2009
DOI: 10.1099/mic.0.030650-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide mediates the fungal-elicitor-enhanced biosynthesis of antioxidant polyphenols in submerged cultures of Inonotus obliquus

Abstract: A fungal elicitor prepared from the cell debris of the plant-pathogenic ascomycete Alternaria alternata induces multiple responses by Inonotus obliquus cells, including an increase in generation of nitric oxide (NO), activity of phenylalanine ammonia lyase (PAL) and accumulation of total mycelial phenolic compounds (TMP), but does not trigger production of oxylipins or jasmonic acid (JA). The role of NO in TMP production was investigated via the effects of the NO-specific scavenger 2-(4-carboxyphenyl)-4,4,5,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…S1A in the Supplementary Material) and supplemented either with 40 μg/l cell wall debris of Alternaria alternata, an elicitor for NO production (Zheng et al 2009a) or 0.1 mM NO donor sodium nitroprusside (SNP) (Sigma, St. Louis, USA), or 40 mM aminoguanidine (AG) (Sigma, St. Louis, USA), the selective inhibitor for nitric oxide synthase. The growth of mycelia (three replicates for each combination) was observed by comparing the area colonized by each fungus along the antagonism front.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1A in the Supplementary Material) and supplemented either with 40 μg/l cell wall debris of Alternaria alternata, an elicitor for NO production (Zheng et al 2009a) or 0.1 mM NO donor sodium nitroprusside (SNP) (Sigma, St. Louis, USA), or 40 mM aminoguanidine (AG) (Sigma, St. Louis, USA), the selective inhibitor for nitric oxide synthase. The growth of mycelia (three replicates for each combination) was observed by comparing the area colonized by each fungus along the antagonism front.…”
Section: Methodsmentioning
confidence: 99%
“…Evidences have shown that NO plays a fundamental role as a signaling molecule regulating normal physiological processes in animal cells and acts as a key player in the regulation of different plant developmental processes (Gas et al 2009;Yu et al 2014). Previously, we have found that increased NO pools resulted in higher accumulation of styrylpyrone polyphenols in I. obliquus (Zheng et al 2009a).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the use of elicitors from microorganisms has been considered to be one of the most effective strategies for improving the productivity of useful secondary metabolites in plant cell cultures (Ciddi et al 1995;Ramani and Chelliah 2007;Xu et al 2005;Zheng et al 2009). In order to examine the effect of PB90 on secondary metabolite production of cultured plant cells, we determined hypericin production of Hypericum perforatum L. cells treated with PB90.…”
Section: Introductionmentioning
confidence: 99%
“…This declared NO plays a regulatory role in the upstream of JA signaling pathway . However, NO is not fully dependent on JA signaling pathway as NO also mediates an elicitor-induced increase in production of antioxidant polyphenols in L obliquus via a signaling pathway independent of oxylipins or JA, a mechanism which differs from those in some higher plants (Zheng et al 2009). Whether these pathways are JA-dependent or not, which may depend on the plant species.…”
Section: The Crosstalk Between Signalingmentioning
confidence: 99%